2013
DOI: 10.1007/s00216-013-6853-x
|View full text |Cite
|
Sign up to set email alerts
|

REMUS100 AUV with an integrated microfluidic system for explosives detection

Abstract: Quantitating explosive materials at trace concentrations in real-time on-site within the marine environment may prove critical to protecting civilians, waterways, and military personnel during this era of increased threat of widespread terroristic activity. Presented herein are results from recent field trials that demonstrate detection and quantitation of small nitroaromatic molecules using novel high-throughput microfluidic immunosensors (HTMI) to perform displacement-based immunoassays onboard a HYDROID REM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This demonstration highlights the numerous advantages of the immunosensor compared to other field deployed TNT sensing platforms: (1) higher sensitivity (parts-per-trillion to ppb levels) and (2) longevity (>18 h of continuous operation) which far exceeds previously published reports to our knowledge [21,22], (3) increased flow rates (up to 9 mL/min) resulting in improved response times (12 s) which compares favorably to many electrochemical detection methods, (4) requires no sample preconcentration which as reported by Trammell and colleagues was necessary to improve sensor sensitivity for trace level detection [23] and most importantly (5) field-durability.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This demonstration highlights the numerous advantages of the immunosensor compared to other field deployed TNT sensing platforms: (1) higher sensitivity (parts-per-trillion to ppb levels) and (2) longevity (>18 h of continuous operation) which far exceeds previously published reports to our knowledge [21,22], (3) increased flow rates (up to 9 mL/min) resulting in improved response times (12 s) which compares favorably to many electrochemical detection methods, (4) requires no sample preconcentration which as reported by Trammell and colleagues was necessary to improve sensor sensitivity for trace level detection [23] and most importantly (5) field-durability.…”
Section: Resultsmentioning
confidence: 73%
“…Each response shown corresponds to a plume simulation of 1–100 ppb TNT emanating from the plume generator where the released TNT was 1.0 ppm. Previous field experiments where the immunosensor payload was integrated with a REMUS AUV to transport and assess TNT composition in seawater suggested that the dilution effect of the seawater with a 2.54 cmseparation between the immunosensor inlet and plume release port could be as high as 100-fold [22]. …”
Section: Resultsmentioning
confidence: 99%
“…Demonstrated within this report is a 128-microchannel microfluidic device that combines intricate architectural designs and biomolecular specificity of an antibody specific for TNT for trace level TNT detection. Evolution of the displacement immunoassay format for TNT from porous membranes [ 23 ], fused-silica microcapillaries [ 24 , 25 ] to microchanneled microfluidic devices [ 20 ] signifies the importance and advantages of maintaining high surface area to volume ratios leading to increased antibody-antigen interactions. Characterization of the 128-microchanneled microfluidic device using COMSOL fluid flow simulations provided greater insight into the fluid dynamics and flow processes.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence displacement immunoassay detection system consisted of the following components: (1) fluorescence spectrofluorometer-Model FP-2020 Plus—was used to measure the displaced fluorescence analog (Cy5-amine–TNB) from the binding pocket of the monoclonal antibody; (2) Rheodyne low pressure three-way-valve injector loop (100 μL) for sample introduction; and (3) two reciprocating pumps (Applied Biosystems, Inc., Foster, CA, USA) for continuous flow at a controlled flow rate (1.0 mL/min). As TNT is introduced into the continuous flow system, preferential binding occurs between the anti-TNT to TNT resulting in the displacement or release of Cy5-amine-TNB from the proteins binding site [ 20 ]. A resultant fluorescence signal (peak) over background is measured and correlated to the TNT concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Mobile robots are meaningful examples of service robots, that are implementing novel key technologies. Mobile robots can be classified by the environment in which they travel, for example UGVs (Unmanned Ground Vehicles) [12], UAVs (Unmanned Aerial Vehicles) [10] and AUVs (Autonomous Underwater Vehicles) [2], or by the device that they use to move as legged robot [11,3], wheeled robot [19,3] and tracked robot [3], or by the work that they do as transportation, mapping, cleaning, assistance and so forth.…”
Section: Introductionmentioning
confidence: 99%